Chemical constituents of stem bark of Croton oblongifolius from Amphoe Phanat Nikhom, Chon Buri Province - Chaiwat Komlaiad (Chulalongkorn University, 2006)
Thesis (M.Sc.)--Chulalongkorn University, 2003